2014
DOI: 10.1111/dsu.12456
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Radiofrequency Ablation for Incompetent Small Saphenous Vein in Terms of Recanalization and Sural Neuritis

Abstract: RFA is an effective and safe treatment modality for incompetent SSV. Peak reflux velocity can be a risk factor for recanalization. Length of RFA segment in SSV does not affect recanalization and postablation sural neuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…Among the treated SSV there was not a single recanalized vein at any time point. It is similar to published short‐term, and better than mid‐term and long‐term data on occlusion rates of RFSA in SSV …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among the treated SSV there was not a single recanalized vein at any time point. It is similar to published short‐term, and better than mid‐term and long‐term data on occlusion rates of RFSA in SSV …”
Section: Discussionsupporting
confidence: 89%
“…It is similar to published short-term, and better than mid-term and long-term data on occlusion rates of RFSA in SSV. 17,20,21 The venous stump persistence has no relevance to the technical outcome of the procedure: the vast majority of successfully ablated saphenous veins are accompanied by a patent stump even 3 years and more after the procedure. The results are similar to our previous DUS findings 2 years after radiofrequency ablation (ClosurePLUS) of 60 GSV.…”
Section: Discussionmentioning
confidence: 99%
“…8 Numerous studies using radiofrequency ablation (RFA) were subsequently published. [9][10][11] Studies comparing endovenous laser ablation (EVLA) and RFA then began being published. These studies generally reported equal success between EVLA and RFA, albeit with fewer side-effects and greater patient satisfaction with RFA.…”
Section: Introductionmentioning
confidence: 99%
“…The SSV is recognized as a potential alternative conduit for coronary artery bypass graft (Cassar et al, ). Many surgical techniques to harvest the SSV have been described in the literature, yet damage to the SN is relatively common (Park et al, ). Thermal ablation of the SSV to treat varicose veins has also been reported to cause injury of the SN and is considered to be a major reason for legal action against vascular surgeons (Campbell et al, ; Ikiz et al, ; Schweighofer et al, ; Rodriguez‐Acevedo et al, ).…”
Section: Introductionmentioning
confidence: 99%